Hakikat Manusia Dalam Kehidupan : Sebuah Pandangan Filosofi - Indah Chintiya Setiyani; Nabilla Safitri; Naya Ramadhani; Thalita Khairani; Wismanto Wismanto; Fitria mayasari (Journal of Student Research, 2025)
KeywoThe background to this study is based on deep knowledge about how humans understand themselves, their relationships with nature and higher entities. Human nature is often the center of attention in various scientific disciplines, including philosophy, religion, psychology, and social sciences, which examine important aspects such as rationality, freedom, morality, and spirituality. The purpose of this research is to find out more about the nature of humans in life, which includes philosophical, moral, social and spiritual backgrounds & about how humans carry out their roles as social creatures, thinking individuals, and entities that have a relationship with nature. Understanding This contributes to the development of insight into the role of humans in creating social, moral and ecological balance in life. The method used in this research is a qualitative method with a literature and case study approach. Data was collected through analysis of various library sources, such as books, articles and scientific journals which discuss theories about human nature, as well as through interviews with thinkers and experts in related fields. This analysis was carried out descriptively and interpretively to gain an in-depth understanding of the concepts that emerged. It is hoped that the results of this research will provide a theoretical contribution to the development of the study of humans and life, as well as provide a practical basis for individuals in leading a balanced life between rational, moral, social and spiritual aspects.